Impact of pH and temperature on the electrochemical and semiconducting properties of zinc in alkaline buffer media. Issue 7 (19th January 2018) - El-Taib Heakal, F.; Abd-Ellatif, W. R.; Tantawy, N. S.; Taha, A. A.
Abstract : The electrochemical and semiconductive properties of spontaneously formed passive films on pure Zn in alkaline buffer solutions. Abstract : The electrochemical and semiconductive properties of spontaneously formed passive films on pure Zn were investigated in alkaline carbonate/bicarbonate buffer solutions as functions of pH and temperature. The study was performed in 0.1 M (CO3 2− + HCO3 − ) mixtures over the pH range 9.2 to 9.8 using open circuit potential, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and Mott–Schottky analysis techniques. Generally, zinc passivation is enhanced with either increasing pH or decreasing the ambient temperature. The steady state potential ( E ss ) value reveals that in pH 9.8 buffer the propensity of Zn for passivation is superior when compared with those in the other tested buffer solutions. The total surface film resistance ( R t ) derived from the impedance data proves this result, which is likely attributed to changes in composition and/or microstructure of the film. In pH 9.8 buffer solution the passivation tendency always decreases with temperature increase. However, in pH 9.2 the system behaves similarly up to 25 °C; afterwards zinc passivation trend was found to re-increase once more. The apparent activation energy for the corrosion process was evaluated and discussed. Analysis of Mott–Schottky plots was found to be suitable for characterizing the semiconductor properties of the naturally deposited barrier layers which are all consistent with the well-known n-type character of the oxide film on zinc. The absence of any evidences for the p-type semiconductive behavior indicates a preponderance of oxygen vacancies and zinc interstitials over metal vacancies. Moreover, Mott–Schottky results demonstrate that the donor concentration increases with either increasing pH or deceasing temperature commensurate with the increasing trends in the passive film thickness.